Perancangan Aplikasi Hasil Belajar Siswa (Rapor) - Adi Febriansyah; Rivan Ahmad Fauzi; Lutfi Nur Farizi Ahmad (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Report card is a web-based application system that is expected to change teacher work patterns from manual patterns to digital patterns and can also make it easier for teachers to conduct assessments of students and even print report cards and evaluate student learning outcomes, e-reports are expected to provide benefits for students, parents and teachers. Through e-reports it is hoped that parents and students will be able to see their children's learning outcomes not necessarily in hardcopy or conventional report cards but can see results by only accessing certain pages that are informed by the school. For teachers who want to enter their grades into reports, they must access online report cards go directly to the school's Raport website. Each teacher has their own account according to the class being taught. In this study, apart from explaining the theoretical studies used as the basis for the preparation, it will also discuss system design and application development. So that it can be expected and implemented in the form of a product that will fix all the deficiencies that existed in the old system.